CARICOM's trade in selected agricultural commodities 2000-2003 (CCS [Georgetown]GY, 2007)
Provides information to users on Trade in Agricultural Commodities by the major headings of the United Nations Standard International Trade Classification (SITC) as well as information on selected commodity details. Focuses on the top five agricultural commodities by Member States for the latest year, 2003.
Keywords: AGRICULTURAL TRADE